2005
DOI: 10.1097/01.ajp.0000125264.40304.8c
|View full text |Cite
|
Sign up to set email alerts
|

Is Temporomandibular Pain in Chronic Whiplash-Associated Disorders Part of a More Widespread Pain Syndrome?

Abstract: The higher prevalence of widespread pain and psychologic distress in patients with chronic whiplash-associated disorder suggests that the higher prevalence of temporomandibular disorder pain in these patients is part of a more widespread chronic pain disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 12 publications
0
14
0
2
Order By: Relevance
“…16,21 Such a rationale is therefore recommended for future studies, as trigeminal sensory disturbances in WAD patients indeed may be part of a widespread phenomenon, in analogy with jaw pain in WAD being part of a widespread pain syndrome. 24 In patients with localized jaw pain and dysfunction, temporomandibular disorders, thermal pain thresholds, but not detection thresholds, were reported to differ from healthy subjects in trigeminal and extra-trigeminal regions. 25 …”
Section: Discussionmentioning
confidence: 99%
“…16,21 Such a rationale is therefore recommended for future studies, as trigeminal sensory disturbances in WAD patients indeed may be part of a widespread phenomenon, in analogy with jaw pain in WAD being part of a widespread pain syndrome. 24 In patients with localized jaw pain and dysfunction, temporomandibular disorders, thermal pain thresholds, but not detection thresholds, were reported to differ from healthy subjects in trigeminal and extra-trigeminal regions. 25 …”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that TMD after a whiplash trauma may develop over time, rather than being part of an acute syndrome . This notion is based on the fact that most studies in acute whiplash patients report a lower prevalence of TMD pain compared with studies based on chronic WAD patient groups . When comparing different study populations after whiplash injury, it should also be remembered that a majority with an acute whiplash injury will recover and that the individuals who develop long‐term symptoms report greater initial pain and disability .…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic three dimensional modelling shows little evidence to support the contention that there is damage to the masticatory apparatus during whiplash (Perez del Palomar and Doblare, 2008). Moreover, it has been suggested that whiplash may lead to widespread body pain and that TMD may just be one expression rather than a specific outcome of whiplash (Visscher et al , 2005).…”
Section: Pathophysiology Of Pompmentioning
confidence: 99%